Synthesis, Antibacterial and Anti-hyperglycemic Activity of Some 6-Substituted Quinoxaline-2,3-diones - Y. PAWAR, PRATAP; B. BHISE, SATISH (Asian Journal of Chemistry, 2010)
A new series of 6-substituted quinoxaline-2,3(1H,4H)-dione bearing sulphaneoamido, thiazolidinone and azomethine moiety were synthesized by treating quinoxaline-2,3(1H,4H)-dione-6-sulfonylhydrazide with substituted aromatic aldehydes to yield N1-(substituted benzylideneamino)-6-(quinoxaline-2,3(1H,4H)-dione sulphanamide (4a-f) which on cyclization with thioglycolic acid in presence of anhydrous zinc chloride afforded 3-[6'-sulpaneoamidoquinoxaline-2',3'(1'H,4'H)-dione-2-(substituted-phenyl]-4-oxothiazolidine (5a-f). All the synthesized compounds were subjected to preliminary in-vitro evaluation for antibacterial activity against various Gram-positive bacterial strains Staphylococcus aureus, Bacillus cereus and Gram-negative strain Pseudomonas aeruginosa and moreover the componuds were also evaluated for their anti-hyperglycemic effect in alloxan induced diabetes in rats.